Nickel Fluorocarbene Metathesis with Fluoroalkenes. (19th April 2018) - Harrison, Daniel J.; Daniels, Alex L.; Guan, Jia; Gabidullin, Bulat M.; Hall, Michael B.; Baker, R. Tom
Abstract: Alkene metathesis with directly fluorinated alkenes is challenging, limiting its application in the burgeoning field of fluoro‐organic chemistry. A new nickel tris(phosphite) fluoro(trifluoromethyl)carbene complex ([P3 Ni]=CFCF3 ) reacts with CF2 =CF2 (TFE) or CF2 =CH2 (VDF) to yield both metallacyclobutane and perfluorocarbene metathesis products, [P3 Ni]=CF2 and CR2 =CFCF3 (R=F, H). The reaction of [P3 Ni]=CFCF3 with trifluoroethylene also yields metathesis products, [P3 Ni]=CF2 and cis / trans ‐CFCF3 =CFH. However, unlike reactions with TFE and VDF, this reaction forms metallacyclopropanes and fluoronickel alkenyl species, resulting presumably from instability of the expected metallacyclobutanes. DFT calculations and experimental evidence established that the observed metallacyclobutanes are not intermediates in the formation of the observed metathesis products, thus highlighting a novel variant of the Chauvin mechanism enabled by the disparate four‐coordinate transition states.